Evaluation of The “Program Pusat Pembinaan dan Latihan Olahraga Pelajar Daerah (PPLPD)” of Riau - Zainur, Zainur; Gazali, Novri (Department of Physical Education, Sport, Health and Recreation, 2019)
Evaluation of this program was to evaluated the Sports Development Program Featured Training Center Student Sports Education Area (PPLPD) Riau Province. Data were collected through observation, q&uestionnaire, interview and document study. The evaluation study conducted in Pekanbaru on PPLPD Riau Provinces ports featured Of Riau Province. This studyused a qualitative approach with descriptive methods and program evaluation research design model of CIPP by Daniel L. Tufflebeam (Contact, the Input-Process and Product). Techniques and procedures for the collection of data through observation, interviews and document studies with data analysis techniques demonstrated on the model CIPP. Results of the evaluation of the over all implementation of the program PPLPD flagship sports (Pencaksilat, sepaktakraw, Rowing and Archery) Riau province was considered to bein accordance with the guidelines for the implementation of PPLPD in improving achievement in accordance withthe objectives of the program PPLPD, between contect. Input, Process hadlinkages and in line with the guidelinesso that the components Productions produced will obtain the expected results of the implementation of the program PPLPD.